The study of 1 MeV electron irradiation induced defects in N-type and P-type monocrystalline silicon. (December 2017) - Babaee, S.; Ghozati, S.B.
Abstract: Despite extensive use of GaAs cells in space, silicon cells are still being used. The reason is that not only they provide a good compromise between efficiency and cost, but also some countries do not have the required technology for manufacturing GaAs. Behavior of a silicon cell under any levels of charged particle irradiation could be deducted from the results of a damage equivalent 1 MeV electron irradiation using the NASA EQflux open source software package. In this paper for the first time, we have studied the behavior of a silicon cell before and after 1 MeV electron irradiation with 10 14, 10 15 and 10 16 electrons-cm −2 fluences, using SILVACO TCAD simulation software package. Simulation was carried out at room temperature under AM0 condition. Results reveal that open circuit voltage and efficiency decrease after irradiation while short circuit current shows a slight increase in the trend around 5 × 10 16 electrons-cm −2, and short circuit current loss plays an important role on efficiency changes rather than open circuit voltage. Highlights: We simulate a silicon solar cell with SILVACO TCAD. Silicon solar cell is irradiated with different fluences of 1 MeV Electron. We studied the trend of Current density-Voltage, Quantum Efficiencies and Power. A slight increase in the short circuit current was observed. Open circuit voltage, quantum efficiencies and maximum output power decrease by increasing fluence.